Pengaruh Persepsi Risiko Dan Kepercayaan Terhadap Minat Menggunakan Payment Linkaja Syariah Pada Generasi Z Karesidenan Madiun Dengan Religiusitas Sebagai Variabel Moderating - Miftakhul Jannah; Ely Masykuroh (Niqosiya: Journal of Economics and Business Research, 2024)
Digital payments are present as a form of technological development in the financialsector which is increasingly accepted by society, especially generation Z, which is a segment with potential for using technology. Even though there is a large Muslim population in Indonesia, interest in using sharia-based digital payments is still low, as evidenced by the number of LinkAja Syariah users which is still considered very low when compared to conventional digital payments. This research uses quantitative methods. The samples taken were 100 respondents. The sampling technique uses purposive sampling technique. The data collection technique uses a questionnaire. The data obtained was then processed using the SPPS 22 application. The analysis techniques used were instrument testing, classical assumption testing, simple linear regression model testing, multiple linear regression, and moderated regression analysis. The results of the research show that partially risk perception has a significant negative effect on interest and trust has a positive and significant effect on interest in using LinkAja Syariah in generation z in Madiun Residency. Based on a simultaneous test, risk perception and trust influence interest in using LinkAja Syariah among generation z in Madiun Residency. Religiosity does not moderate the risk perception of interest. And religiosity does not moderate trust in interest in using LinkAja Syariah payments among generation z in Madiun Residency.